Determining the Preventive Effect of Topical Magnesium Sulfate Administration on Postoperative Sore Throat [Letter] - Guan YF; Huang ZB; Xue FS (Drug Design, Development and Therapy)
Yu-Fu Guan,1 Zhi-Bin Huang,2 Fu-Shan Xue2,3 1The First Clinical School of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fuzhou University Affiliated Provincial Hospital, Fujian Provincial Hospital, Fuzhou, People’s Republic of China; 3Department of Anesthesiology, Beijing Anzhen Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Fu-Shan Xue, Email xuefushan@aliyun.com; fushanxue@outlook.com